Expanding our understanding of the role of peer support in child welfare workforce retention. Issue 1 (1st January 2020) - Sedivy, Jennifer A.; Rienks, Shauna; Leake, Robin; He, Amy S.
ABSTRACT: Turnover is problematic for child welfare agencies and clients. To better understand the role of peer support in retention among caseworkers, this study explored whether staff perceive distinct types of peer support (operational and social-emotional) and examined the extent to which peer support differs by demographic and organizational factors in predicting intent to stay. Results from 1, 703 caseworkers indicated that they perceive both types of peer support; both types are associated with job satisfaction, organizational climate, and intent to stay. Strategies to bolster peer support and opportunities for future research are discussed.